Behavior of Glulam Beams Strengthened in bending with BFRP Fabrics - Wdowiak-Postulak, Agnieszka; Świt, Grzegorz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents results of an experimental studies on reinforcement of pine beams made from glued laminated timber with subsurface basalt fibers (BFRP). An experimental research program was presented, in which the bending strength of glued laminated timber of middle and lower quality class was increased after using BFRP basalt fabrics.
Keywords: glued laminated timber; natural materials; BFRP fabric; reinforcements; bending strength; drewno klejone warstwowo; materiały naturalne; BFRP; wzmocnienia